KEADAAN PEMENUHAN HAK PENDIDIKAN ANAK REMAJA PASCA REUNIFIKASI - Nurliana Cipta Apsari; R. Nunung Nurwati (Universitas Padjadjaran, 2017)
ABSTRACTFamily is the first and utmost place for child rights fulfilment. Commonly, family is the place to guarantee the development and child rights fulfilment, however, many children are being placed in orphanages in order for the children to acquire their rights of education. Children reside in orphanages are vulnerable of discrimination. In order to protect the vulnerable children, Save the Children with its program of Child and Family Support Center (PDAK) returning children residing in orphanages into their families, known as reunification, to receive family based care and still acquiring their rights including rights of education. Sequential mixed of quantitative and qualitative approach is used in this research. Data is collected from children and parents involved with reunification process and child care. The focus of this research is the fulfillment of child rights to develop and survival, mainly rights of education.The result shows that after reunification, one youth is not pursuing his study and decided to work because his father could not afford the educational expenses. The result also found that although the parents are economically deprived, but no youth have return to orphanages to receive institution based care. The research found strength of parent and resiliency of children thus keeping the children reside in their family and receive family based care. The strength of parent and child resilience exists because of social work support through case management model of PDAK Save the Children. The social workers have assisted the parents to gain access needed in order for them to fulfill the child rights. The social workers also assist and provide understanding to the children about their parents’ condition which then resulting in child resilience. Case management model serves as model for direct services for children and their families in keeping the continuity of family based care received by children after reunification. With this model, service providers will be able to synergized the policies and programs of social insurance planned and implemented by the government thus overcoming the limited access of parents to fulfill their children’s rights.